1995
DOI: 10.1007/bf02869958
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive kinetic, thermodynamic and photochemical study of some spiro-indoline-oxazines

Abstract: The thermoreversible photochromic reaction of spiro-indolineoxazines to photo-merocyanines has been studied by stationary spectrophotometric techniques. Two methods are described for determining the molar absorption coefficient of the metastable photomerocyanine and the quantum yield of the colour-forming photoreaction. Kinetic parameters (reaction rate and activation energy) and thermodynamic quantities (equilibrium constant and enthalpy) of the thermal reaction have also been determined. Based on the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
1
10
1
Order By: Relevance
“…The equilibrium constants for the thermal coloration of the spirooxazines ranged from 10 À2 to 10 À4 and were strongly structure-and solvent-dependent. 10,11 In the present case, the phenomenon is less evident due to a somewhat higher DH 0 value and lower molar absorption coefficient of the coloured form than those of spirooxazines, for which the forward reaction is endothermal by 10-20 kJ mol À1 , , while e (50 000-70 000 dm 3 mol À1 cm À1 ) of the open coloured form is about 2-3 times larger.…”
Section: Methodscontrasting
confidence: 52%
See 2 more Smart Citations
“…The equilibrium constants for the thermal coloration of the spirooxazines ranged from 10 À2 to 10 À4 and were strongly structure-and solvent-dependent. 10,11 In the present case, the phenomenon is less evident due to a somewhat higher DH 0 value and lower molar absorption coefficient of the coloured form than those of spirooxazines, for which the forward reaction is endothermal by 10-20 kJ mol À1 , , while e (50 000-70 000 dm 3 mol À1 cm À1 ) of the open coloured form is about 2-3 times larger.…”
Section: Methodscontrasting
confidence: 52%
“…(2). 10,11 In this equation the denominator, (C 0 À A T /e T ), can be approximated to C 0 considering the very low concentration of T in thermal equilibrium with BFP. Assuming that the spectrum of the thermally equilibrated coloured form T is similar to that of the photoproduced coloured form P, a K value on the order of 10 À3 was estimated at 298 K.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in one of the first studies 184 devoted to the detailed investigation of the kinetics of photoinduced processes in SPO molecules, the authors considered spiroindolinonaphthooxazines containing electron-donating substituents at position 6 H and concluded that the reverse photoreaction could be ignored because the ratio of the quantum yields of the reverse and forward photoreactions is in the range of 0.03 ± 0.07. In more recent studies 166,168,185 of the kinetics of photoinduced reactions of SPO, whose molecular structures differ from those studied earlier, the authors also ignored the reverse photoreaction with the unjustified reference to the results of the study. 184 An approach which involves the numerical integration of differential equations using the Runge ± Kutta method and an iteration procedure using the Powell minimisation algorithm shows more promise.…”
Section: Photochemical Properties Of Spirooxazinesmentioning
confidence: 99%
“…taking into account only two or three processes instead of four . There are several examples in the literature of quantitative descriptions of two-process (I + II and II + IV) or three-process (I + II + III and I + II + IV) photo- or thermochromic systems. However, quantitative analysis of complete four-process systems remains to be achieved.…”
Section: Introductionmentioning
confidence: 99%